Mercury Pollution in Minamata - Hisashi Yokoyama (SpringerBriefs in Environmental Science, 2018)
It overviews the poisoning which occurred in the 1950s and 1960s among the residents in Minamata who ate seafood contaminated with methylmercury discharged from the chemical factory, Chisso Corporation. It describes the history, symptoms pathogenesis and research on the causal agent, and discusses the responses of Chisso and the national and local governments to the outbreak, the victims, the compensation and environmental restructuring as well as the court ruling on claims. Based on lecture notes from a university course, it includes students' suggestions for avoiding a repeat of the tragedy. The issue has not been settled yet, and this analysis of the incident provides useful insights into solutions to the current global mercury pollution problem.